Testing of biological and chemical preparations against Obolodiplosis Robiniae and Euura tibialis in the conditions of Yerevan city - Babayan, A. H.; Hovhannisyan, V. S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Chemical and bacterial preparations have been tested in order to fight against Robinia pseudoacacia pests Obolodiplosis robiniae and Euura tibialis, some of the most widely spread fragrant tree species in Yerevan gardens. Among the preparations used against E. Tibialis, the highest biological efficiency was registered by the chemical preparation of antion (94,0 %) with a consumption rate of 1.7 l/ha, and Bacillus thuringiensis strain (91,0 %) with a concentration of 3 l/ha among the bacterial preparations. In the case of O. robiniae, high result (94,0 %) was registered by acpeline at the rate of consumption of 1 l/ha, and again the Bt 26-70 (85,4 %) strain at a rate of 3 l/ha among the bacterial preparations. Երևանի այգիներում տարածված բուրումնավետ ծառատեսակներից՝ կեղծ ակացիայի վնասատուներ սպիտակ ակացիայի գալամլակի (Obolodiplosis robiniae) և ակացիայի սղոցողի (Euura tibialis) դեմ պայքարի նպատակով փորձարկվել են քիմիական և բակտերիական պատրաստուկներ: E. tibialis -ի դեմ կիրառվող միջոցներից առավել բարձր կենսաբանական արդյունավետություն գրանցել է 1,7 լ/հա ծախսի նորմայով անթիո (94,0 %) քիմիական պատրաստուկը, իսկ բակտերիական պատրաստուկներից 3լ/հա խտանյութ չափաքանակով Bacillus thuringiensis 26-70-ը (91,0%) շտամը: O. robiniae -ի դեպքում բարձր արդյունք (94,0 %) դրսևորել է ակպելինը՝ 1լ/հա ծախսի նորմայով, իսկ բակտերիական պատրաստուկներից կրկին 3 լ/հա խտանյութ չափաքանակով Bt 26-70-ը (85,4 %) շտամը: Для борьбы вредителей (E. tibialis и O. robiniae) ложной акации, одного из наиболее широко используемых душистых деревьев в ереванских садах были испытаны химико-бак-териальные препараты. Среди средств, применяемых против вредителя E. tibialis, наиболь-шую биологическую эффективность зарегистрировал химический препарат антио (94,0 %) при норме расхода 1,7 л/га и штамм Bt 26-70 при концентрации 3 л/га. (91,0 %). В случае Obolodiplosis robiniae результат был высоким (94,0 %) при норме 1 л/га акпелина, а также при норме 3 л/га концентрата из бактериологических препаратов Bt 26-70 (85,4 %).
Keywords: Biology